Assessment of exocrine pancreatic function in children and adolescents with direct and indirect testing - Hopson, Puanani; Smadi, Yamen; Mehta, Vijay; Patel, Samit; Mehta, Devendra; Horvath, Karoly (Frontiers in Pediatrics, 2022)
The exocrine pancreas plays an important role in digestion. Understanding of the physiology and regulation of exocrine function provides insight into disease processes and basis of functional testing. Specifically, exocrine pancreatic insufficiency (EPI) can cause maldigestion and thus a proper assessment of exocrine pancreatic function is important. There are indirect and direct methods for evaluating pancreatic function. Indirect methods are varied and include stool, serum, urine, and breath tests. Fecal elastase is a commonly used indirect test today. Direct methods involve stimulated release of pancreatic fluid that is collected from the duodenum and analyzed for enzyme activity. The most used direct test today is the endoscopic pancreatic function test. Indirect pancreatic function testing is limited in identifying cases of mild to moderate EPI, and as such in these cases, direct testing has higher sensitivity and specificity in diagnosing EPI. This review provides a comprehensive guide to indirect and direct pancreatic function tests as well as an in-depth look at exocrine pancreatic function including anatomy, physiology, and regulatory mechanisms.